Research on induction generators for isolated rural applications: State of art and experimental demonstration. (December 2022) - Duvvuri, SSSR Sarathbabu; Sandeep, V.; Yadlapati, Kishore; Krishna, V.B Murali
Abstract: -Asynchronous machines/Induction machines are one of the leading machines in the electrical sector and which are well suitable for the motoring and generating applications of a few kilowatts rating to megawatt ratings. Research on induction machines for generating applications is drawing attention among the researchers due to its low cost, rugged construction, brushless arrangement and all. The operation of induction generator (IG) is quite interesting and which is different for grid and off-grid mode of operation. The IG for the off-grid applications (so called self-excited induction generator, SEIG) requires an additional reactive power supply for the successful build-up of voltage and as well as for supplying the electric loads. On the other hand, load power balance is also one the challenges since off-grid systems are directly connected to the loads. In this context, many researches have been reported the different approaches and techniques for the successful and economical operation of IG for small scale off-grid power generation. In this paper, an exclusive analytical study is presented on the excitation requirement and load balance phenomena of self-excited induction generator (SEIG). Further, a basic experimental setup of renewable energy source driven SEIG system and its operation for the electric power generation is demonstrated and the same is simulated by using MATLAB/Simulink.